Local Nucleon-Nucleon and Three-Nucleon Interactions Within Chiral Effective Field Theory - Piarulli, Maria; Tews, Ingo (Frontiers in Physics, 2020)
To obtain an understanding of the structure and reactions of nuclear systems from first principles has been a long-standing goal of nuclear physics. In this respect, few- and many-body systems provide a unique laboratory for studying nuclear interactions. During the past decades, the development of accurate representations of the nuclear force has undergone substantial progress. Particular emphasis has been devoted to chiral effective field theory (EFT), a low-energy effective representation of quantum chromodynamics (QCD). Within chiral EFT, many studies have been carried out dealing with the construction of both the nucleon-nucleon (NN) and three-nucleon (3N) interactions. The aim of the present article is to give a detailed overview of the chiral interaction models that are local in configuration space, and show recent results for nuclear systems obtained by employing these local chiral forces.